A landmark event: Faculty of Medicine hosts master of rehabilitation medicine examination for the first time - Zainudin, Muhamad Faizal; Ngimron, Anie Farhana; Mohd Mustafah, Nadia; Wan Mohd Zohdi, Wan Najwa; Omar, Mazlifah; Mohamad Hashim, Natiara; Ahmad Roslan, Nor Faridah (Faculty of Medicine, 2025)
The importance of rehabilitation medicine in modern healthcare cannot be overstated. As populations age and chronic diseases become increasingly prevalent, rehabilitation plays a crucial role in enhancing quality of life and promoting functional independence. It is estimated that one in three people worldwide will require rehabilitation at some point in their lifetime 1. In Malaysia, this equates to nearly 10 million individuals who could benefit from such services 2.